Physiology of the elite rower
In this article author tries to provide an overview of the specific physiological characteristics of successful rowers. CHAPTER 1: The rowing stroke, SIZE and SHAPE CHAPTER 2: Physiological characteristics of elite rowers-maximal oxygen consumption CHAPTER 3: Skeletal muscle characteristics